'Never be dull': Girl Guides of Canada performing physical culture and gymnastics drills in 1910–21 - Fitzsimmons Frey, Heather (My University, 2020)
In their first decade of operation in Canada, Canadian Girl Guides presented numerous performances, primarily as fundraisers, to raise money for the Red Cross or to go to camp. Their performances included a great deal of variety, and often gymnastics drills. While critics suggest that these drills were joyless affairs, girls chose to do them, and many probably took pleasure and pride in developing the choreography and performing them well. Preliminary research with twenty-first-century girls shows that developing the drills can be a lot of fun, and that the movement vocabulary has considerable creative potential. Performing the drills in early twentieth-century communities could challenge expectations about differences between boys and girls while demonstrating girls’ strength, emphasize a hopeful future full of healthy (probably white) girls who would become healthy mothers, and encourage audiences to think about unity. In the early twentieth century, Guides would have been unlikely to have seen a professional physical culture drill. With no professional counterpart, girls could not really be amateurs, but it is important that girls probably had to imagine the best drill possible.
Keywords: Girl Guides of Canada; performances; drills